An Adaptively Biased Linear MOS Transconductor for Low Power Application - Tongpoon, Pravit (วารสารวิชาการ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2019)
An adaptively biased linear MOS transconductor is known as a linear transconductor. However, if the low transconductance is needed, small operating current makes MOSFETs operate in weak inversion. In this case, the voltage-current characteristic is not expressed as a square-law characteristic but is expressed as an exponential function. Thus, the factor makes linearity of the transconductor worse. In this paper, a new design of the adaptively biased linear MOS transconductor considering the inﬂuence of MOSFETs operating in weak inversion is proposed. In the proposed technique, an adaptive biasing circuit is newly designed for improvement of the linearity deterioration. Simulation results show that the proposed technique is effective for improvement of the linearity.